Drotaverine for Acceleration of Labour with Reduced Incidence of Caerserean Section and No Postpartum Haemorrhage - AQUILA FAZIL, NADIA SABEEN, FARZANA LATIF (Journal of Fatima Jinnah Medical University, 2018)
Aims & Objectives: To compare the outcome in labouring patients receiving drotaverine versus control group. Setting: Department of Obs & Gynae Unit-III Services Hospital, Lahore. Study Design: Randomized controlled drug trial. Sampling Technique: Simple Random sampling.Duration of Study:12-10-14 to 11-04-15 Subjects and Methods: A total of 200 patients (100 in each group) were included in the study. group-A was given 40mg of intravenous drotaverine in first stage of labour during active phase and its effect was assessed by calculating the time in minutes to reach the full dilatation of cervix while group-B did not receive any drug and used as control group. The dose was repeated after 2 hours, if the rate of dilatation of cervix was less than 1cm/hr in primigravida and 1.5cm/hr in multigravida. Patients were monitored in postnatal period in first 24 hours for postpartum haemorrhage in both the groups as per operational definitions. Results were recorded on spss version for final analysis. Results: patients were ranged between 20-40 years of age. Mean age of the patients was 22.51±4.70 and 26.20±4.55 years in group-A and B, respectively. Mean gestational age was 39.35±1.08 weeks in group-A and 39.59±0.99 weeks in group-B. Postpartum haemorrhage was occurred in 13 patients (13.0%) of group-A and 14 patients (14.0%) of group-B. In group-A, 93 patients (93.0%) and in group-B, 76 patients (76.0%) vaginal delivery performed while in 7 patients (7.0%) of group-A and in 24 patients (24.0%) of group-B caesarean section was carried out. There was statistically significant difference between the two groups (p=0.001). In group-A 56 ladies (56.0%) and in group-B 51 ladies (51.0%) were primigravida while 44 ladies (44.0%) in group-A and 49 ladies (49.0%) in group-B were multigravida. Mean duration of first stage of labour was 206.80±24.45 and 308.40±48.69 in group-A and B, respectively (p<0.001). Stratification with regard to parity was carried out. Conclusion: In Conclusion, The Use Of Drotaverine Hydrochloride During The active phase of first Stage Of Labor Is safe And Effective In Accelerating Labour. Its timely Administration during first stage of labour helps in faster and smooth progress Of Labor With faster Cervical Dilatation and minimal side effects.